2012
DOI: 10.9734/ajea/2012/963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Leaf Positions on Some Micronutrients, Anti-nutrients and Toxic Substances in Telfairia occidentalis at the Vegetative Phase

Abstract: Pot experiment was conducted to determine the effect of leaf positions on the concentrations of some phytotoxins (cyanide, nitrate, soluble and total oxalates), micronutrients namely; vitamin C, β-carotene (provitamin A) and mineral elements (Fe, Mg, Cu, Zn, Ca Na and K) at vegetative phase of Telfairia occidentalis grown in nitrogen and non -nitrogen treated soil. The leaves of Telfairia occidentalis were harvested and analysed at three different leaf locations, namely; basal, middle and upper positions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
6
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
5
6
1
Order By: Relevance
“…High Vitamin C (220.41 mg/100g) content was noted in basal whorl leaves on 120 days and lesser value (92.26 mg/100g) in terminal leaves on 60 days. Similar trend was observed in Telifairia occidentalis by [18] Platel and Srinivasan (2017) and [5] Musa et al (2012). The previous study in Chekkurmanis by [22] Padmavathi and Rao (1990) and [31] Singh et al (2011) reported that vitamin C content was 244.00 mg/100g and 314.30 mg/100g respectively in terminal and basal whorls, which was higher than this study result.…”
Section: Vitamin Csupporting
confidence: 84%
“…High Vitamin C (220.41 mg/100g) content was noted in basal whorl leaves on 120 days and lesser value (92.26 mg/100g) in terminal leaves on 60 days. Similar trend was observed in Telifairia occidentalis by [18] Platel and Srinivasan (2017) and [5] Musa et al (2012). The previous study in Chekkurmanis by [22] Padmavathi and Rao (1990) and [31] Singh et al (2011) reported that vitamin C content was 244.00 mg/100g and 314.30 mg/100g respectively in terminal and basal whorls, which was higher than this study result.…”
Section: Vitamin Csupporting
confidence: 84%
“…Ogbadoyi (2012) have investigated the leaf position influence on the iron level in this vegetative organ in Telfairia occidentalis Hook. f. (Cucurbitaceae), using both a control soil and a nitrogen-fertilized one [ 52 ]. Their results suggest that nitrogen supply slightly increases iron absorption, but the authors conducted no statistical inference test (applying t-tests on data published we have found that the differences were not significant, however consistent across the three leaf positions, which indicates that increasing the sample size might result in statistical significance, currently this being a hypothesis only, yet to be confirmed).…”
Section: Resultsmentioning
confidence: 99%
“…They may be aromatic, bitter or tasteless [4], generally succulent and consumed as a side dish with starchy staples [5]. The green leaves of vegetables are rich in retinol (vitamin A), vitamin B complex, folic acid, vitamin C, and mineral elements such as calcium, iron, zinc, potassium, copper, magnesium, and phosphorus [6][7][8][9][10]. In the world today, there are several reports on the nutritional benefits of vegetable species; one of these includes Pterocarpus soyauxii and Pterocarpus santalinoides [9][10][11].…”
Section: Introductionmentioning
confidence: 99%